Energy hub optimization framework based on open-source software & data - review of frameworks and a concept for districts & industrial parks - Groissböck, Markus (International Journal of Sustainable Energy Planning and Management, 2021)
Multi-model energy systems are gaining importance in a world where different types of energy, such as electricity, natural gas, hydrogen, and hot water, are used to create more complex but also more economic energy systems to support deep decarbonization. While the research community is using open source for a long-time collaborative work on open-source tools is not yet the norm within the research community. To increase the open and sharing efforts between research organizations governments are driving publicly funded projects to share their outcomes. The proposed open-source framework is based on the principle of maximizing the reuse of existing data, software snippets and packages, and add individual code only as necessary. A screening of more than hundred software packages identified six suitable open-source frameworks to be partly incorporated into the new open-source framework. The best parts of each of these frameworks are combined in a way that utilizes limited human resources in an optimal way. To further improve the so created energy system framework additional features such as a scenery model to incorporate shadowing and elevation effects on conventional and renewable power generation technologies are included. Going forward, this approach allows to expand research into urban air assessment in which traffic and energy emissions can be assessed jointly.